2022
DOI: 10.5006/4094
|View full text |Cite
|
Sign up to set email alerts
|

Development of the NACE “MR-01-75” and NACE “TM-01-77” Standards, Part II: Accelerated Material Qualification Testing in Sour Environments at Near Atmospheric Pressure

Abstract: This paper is Part II of a two-part series intended to narrate the history, some of which has been forgotten over time, leading up to the publication of the first Material Requirement (MR-01-75) standard prepared by NACE and its subsequent auxiliary standards. Previously, Part I described the field observations and discussed the metallurgical factors that were being investigated by the historical NACE T-1B and 1F committees to support the development a of sour service materials standard. In Part II, we focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, Q&T processing could improve SSC resistance by decreasing residual stress. In addition, it is recognized that SSC failure only occurs in steel with a hardness value higher than 22 HRC or 248 HV; otherwise, the peak C H value at high-concentration regions is insufficient to generate SSC failure [41][42][43]. The measured hardness values of the matrix and the carbon-rich banded structures for the initial hot-rolled specimens corresponded to ~190 HV and ~260 HV, respectively, while that of the matrix for the Q&T specimens corresponded to ~220 HV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Q&T processing could improve SSC resistance by decreasing residual stress. In addition, it is recognized that SSC failure only occurs in steel with a hardness value higher than 22 HRC or 248 HV; otherwise, the peak C H value at high-concentration regions is insufficient to generate SSC failure [41][42][43]. The measured hardness values of the matrix and the carbon-rich banded structures for the initial hot-rolled specimens corresponded to ~190 HV and ~260 HV, respectively, while that of the matrix for the Q&T specimens corresponded to ~220 HV.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Q&T processing could improve SSC resistance by decreasing residual stress. In addition, it is recognized that SSC failure only occurs in steel with a hardness value higher than 22 HRC or 248 HV; otherwise, the peak CH value at high-concentration regions is insufficient to generate SSC failure [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been recognized in the applicable codes that the SSC become a problem only when the steel has a hardness higher than 248 HV, which is equivalent to 22 HRC. [5,31] Unless the steel is hard enough, the peak C H at the high-concentration region is insufficient to cause the SSC. Table 3 lists the Vickers hardness of both the ferrite matrix region and the banded structure region in microstructure.…”
Section: The Influence Of the Banded Structure On Ssc Resistancementioning
confidence: 99%
“…[3,4] For conventional industrial applications, steels with the hardness of higher than Rockwell hardness (HRC) 22 (equivalent to 550 MPa YS) are thought to have high sulfide stress cracking (SSC) susceptibility. [5] Just from a strength point of view, the SSC cracking of the Q345 pressure vessel steel does not seem to be a concern even when applied in sour oil and gas environments containing H 2 S. Unfortunately, however, practical service experience indicated that the Q345 pressure vessel steel might suffer from SSC failure in wet H 2 S environments. A concern on the SSC failure is valid for this steel as applied in sour oil and gas environments containing H 2 S. The general opinion is that hydrogen ingress can occur under the condition that allows a release of hydrogen.…”
Section: Introductionmentioning
confidence: 99%